A humanism for nursing?. Issue 2 (17th January 2019) - McCaffrey, Graham
Abstract: Humanism has appeared intermittently in the nursing literature as a concept that can be used in understanding nursing. I return to the concept in response to noticing the term appearing in the context of health humanities, where it is loosely associated both with humanities and being humane. I review the usage and critiques of humanism in both nursing and medical literature and then re‐evaluate what the idea of humanism might hold for nursing, trying to avoid the traps of an over‐determination of the human subject, or dichotomizing nursing as art or science, technology or caring. I draw on writings on humanism primarily from Emmanuel Levinas and Edward Said to emphasize strands in humanism of obligation towards others and of critical discernment within history and culture directed towards democratic practices. I discuss in passing the strong association in the UK particularly between humanism and scientism as a note of caution about the plurality of the term humanism. I conclude that humanism is a tradition that does offer productive ways of thinking about nursing with the proviso that it ought to be treated carefully as a problematic tradition and not as a new essence for nursing.